How the West Stole Democracy From the Arabs : The Syrian Congress of 1920 and the Destruction of its Historic Liberal-Islamic Alliance - Thompson, Elizabeth F. (London Grove Press UK, 2021)
The story of a pivotal moment in modern world history, when representative democracy became a political option for Arabs - and how the West denied the opportunity.
Include Illustrations and Index
Keywords: Syria -- Arab nationalism -- Arab countries -- Lawrence, T. E. (Thomas Edward), 1888-1935 -- Middle East -- Syria -- History -- French occupation, 1918-1946